Operationalizing Ecotheology through Embodied Ecological Practice: A Community Empowerment Approach - Reni, Dewi Susilo; Prasetiyo, Eko (LP2M Institut Agama Islam Ngawi, 2026)
Environmental degradation has emerged as one of the most pressing global challenges of the contemporary era, manifested in ecological imbalance, excessive exploitation of natural resources, and declining environmental quality. These conditions suggest that environmental crises cannot be addressed solely through technical or economic solutions, but must also be understood as moral and spiritual challenges rooted in human–nature relationships. This study explores how ecotheological values can be operationalized through embodied ecological practice to support sustainable community empowerment. Employing a qualitative, participatory, and practice-based approach, the study integrates ecotheological reflection with eco-friendly creative practices, using ecoprint as an illustrative form of embodied ecological praxis. Community engagement is accompanied by reflective dialogue on environmental ethics and stewardship, enabling participants to connect practical activities with moral and spiritual values. The findings indicate enhanced ecological awareness, strengthened ethical orientation toward environmental care, and the emergence of sustainable livelihood perspectives aligned with ecological responsibility. This study demonstrates that ecoprint can function not only as an environmentally friendly production technique, but also as a mediating practice for translating ecotheological ethics into lived community experience. By bridging ethical values, embodied practice, and reflective engagement, the study contributes to interdisciplinary discussions on value-based sustainability and community empowerment.